2018
DOI: 10.3389/fnmol.2018.00003
|View full text |Cite
|
Sign up to set email alerts
|

Mitochondrial Division Inhibitor 1 (mdivi-1) Protects Neurons against Excitotoxicity through the Modulation of Mitochondrial Function and Intracellular Ca2+ Signaling

Abstract: Excessive dynamin related protein 1 (Drp1)-triggered mitochondrial fission contributes to apoptosis under pathological conditions and therefore it has emerged as a promising therapeutic target. Mitochondrial division inhibitor 1 (mdivi-1) inhibits Drp1-dependent mitochondrial fission and is neuroprotective in several models of brain ischemia and neurodegeneration. However, mdivi-1 also modulates mitochondrial function and oxidative stress independently of Drp1, and consequently the mechanisms through which it … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
74
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 82 publications
(76 citation statements)
references
References 60 publications
2
74
0
Order By: Relevance
“…DRP1 and mitochondrial fission 1 protein (FIS1) are the main mitochondrial fission mediators (Frezza et al, ). We used the mitochondrial fission inhibitor Mdivi‐1 (Ruiz, Alberdi, & Matute, ) as the high (100 ng/mL) dose of LPS induced an increase in fragmented mitochondria (Figure b). We examined the effect of pharmacologically blocking mitochondrial fission in LPS‐exposed microglia cells cultured from Cox8/EGFP mice by pretreatment with 25 μM Mdivi‐1 for 1 hr followed by incubation with LPS (100 ng/mL) for 24 hr.…”
Section: Resultsmentioning
confidence: 99%
“…DRP1 and mitochondrial fission 1 protein (FIS1) are the main mitochondrial fission mediators (Frezza et al, ). We used the mitochondrial fission inhibitor Mdivi‐1 (Ruiz, Alberdi, & Matute, ) as the high (100 ng/mL) dose of LPS induced an increase in fragmented mitochondria (Figure b). We examined the effect of pharmacologically blocking mitochondrial fission in LPS‐exposed microglia cells cultured from Cox8/EGFP mice by pretreatment with 25 μM Mdivi‐1 for 1 hr followed by incubation with LPS (100 ng/mL) for 24 hr.…”
Section: Resultsmentioning
confidence: 99%
“…Mdivi-1 reduces ischemia-reperfusion (IR) injury in the kidney 6 and heart by inhibiting pathologic fission, thereby decreasing the production of reactive oxygen species (ROS). 13,14 Therefore, we wanted to discover additional more potent and specific Drp1 GTPase inhibitors that are orally bioavailable and nontoxic for use in the treatment of cardiovascular diseases and cancer. 10,11 Coordinated mitochondrial fission that accompanies cell division (mitosis) is called mitotic fission and inhibition of mitotic fission causes cell cycle arrest.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, there is some evidence linking excitotoxic conditions to ISR. Neurons exposed to kainate [ 23 ] and NMDA [ 24 , 25 ] showed a phosphorylation of eIF2α and in both cases excitotoxicity was attenuated by salubrinal, which enhances both constitutive (GADD34-independent) and stress-induced (GADD34-mediated) ISR. Importantly, Milhaud et al [ 26 ] reported that guanabenz and other imidazolines inhibit NMDARs in a non-competitive manner and exert neuroprotection against excitotoxicity.…”
Section: Introductionmentioning
confidence: 99%